The multidimensionality of soil macroecology - Eisenhauer, Nico; Buscot, François; Heintz‐Buschart, Anna; Jurburg, Stephanie D.; Küsel, Kirsten; Sikorski, Johannes; Vogel, Hans‐Jörg; Guerra, Carlos A.; Kivlin, Stephanie (Global ecology and biogeography, 2021)
The recent past has seen a tremendous surge in soil macroecological studies and new insights into the global drivers of one‐quarter of the biodiversity of the Earth. Building on these important developments, a recent paper in Global Ecology and Biogeography outlined promising methods and approaches to advance soil macroecology. Among other recommendations, White and colleagues introduced the concept of a spatial three‐dimensionality in soil macroecology by considering the different spheres of influence and scales, as soil organism size ranges vary from bacteria to macro‐ and megafauna. Here, we extend this concept by discussing three additional dimensions (biological, physical, and societal) that are crucial to steer soil macroecology from pattern description towards better mechanistic understanding. In our view, these are the requirements to establish it as a predictive science that can inform policy about relevant nature and management conservation actions. We highlight the need to explore temporal dynamics of soil biodiversity and functions across multiple temporal scales, integrating different facets of biodiversity (i.e., variability in body size, life‐history traits, species identities, and groups of taxa) and their relationships to multiple ecosystem functions, in addition to the feedback effects between humans and soil biodiversity. We also argue that future research needs to consider effective soil conservation policy and management in combination with higher awareness of the contributions of soil‐based nature's contributions to people. To verify causal relationships, soil macroecology should be paired with local and globally distributed experiments. The present paper expands the multidimensional perspective on soil macroecology to guide future research contents and funding. We recommend considering these multiple dimensions in projected global soil biodiversity monitoring initiatives.